Seeing through the Ground: The Potential of Gravity Gradient as a Complementary Technology - N. Metje; D. N. Chapman; C. D. F. Rogers; K. Bongs (Advances in Civil Engineering)
In the UK there is a huge legacy of buried utility service pipelines and cables beneath our streets and new services, such as fibre optic cables, are being added all the time. Much of this utility network is poorly mapped and recorded. It is therefore important to accurately locate and map these services to aid the installation of new, and repair and maintenance of existing, assets. This will help avoid damage to adjacent services and reduce the direct and social costs associated with finding buried utilities. This paper describes two major UK initiatives—Mapping the Underworld (MTU) and Gravity Gradient Technologies and Opportunities Programme (GG-TOP)—that aim to improve the way that we locate, map, and share information on buried utility services. MTU aims to develop a multisensor device to locate buried services, while GG-TOP aims to develop gravity gradient technology to deliver a (three orders of magnitude) step change in performance.